Silicon photonic beam steering module with backside coupling elements toward dense heterogeneous integration with drive electronics - X. Chen (AIP Publishing LLC, 2021)
Solid state beam steering devices are key elements in low cost, robust, and three-dimensional imaging systems. Here, we present a silicon photonic beam steering device based upon an 8 × 8 grating coupler focal plane array approach fed by a thermo-optic Mach–Zehnder switching tree. In this device, transmission of light from the grating couplers is made through the backside of the chip using topside mirrors allowing for both high-efficiency out-coupling and direct flip-chip integration of drive electronics, providing a path to scale to denser focal plane arrays with large numbers of points in the future. A −13.8 dB fiber-to-fiber transmission was achieved in our preliminary test around 1523 nm for the beam steering chip.